Effect of tumor microenvironment on pathogenesis of the head and neck squamous cell carcinoma: a systematic review - Peltanova, Barbora; Raudenska, Martina; Masarik, Michal (Molecular cancer, 2019)
The tumor microenvironment (TME) is comprised of many different cell populations, such as cancer-associated fibroblasts and various infiltrating immune cells, and non-cell components of extracellular matrix. These crucial parts of the surrounding stroma can function as both positive and negative regulators of all hallmarks of cancer development, including evasion of apoptosis, induction of angiogenesis, deregulation of the energy metabolism, resistance to the immune detection and destruction, and activation of invasion and metastasis. This review represents a summary of recent studies focusing on describing these effects of microenvironment on initiation and progression of the head and neck squamous cell carcinoma, focusing on oral squamous cell carcinoma, since it is becoming clear that an investigation of differences in stromal composition of the head and neck squamous cell carcinoma microenvironment and their impact on cancer development and progression may help better understand the mechanisms behind different responses to therapy and help define possible targets for clinical intervention.
Keywords: nádorové mikroprostředí; Animals; Carcinoma, Squamous Cell; lidé; Disease Progression; Head and Neck Neoplasms; Tumor Microenvironment; Humans; spinocelulární karcinom; progrese nemoci; nádory hlavy a krku; zvířata